2009
DOI: 10.1152/ajpheart.01016.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of α1-adrenergic vasoconstriction in the regulation of skeletal muscle blood flow with advancing age

Abstract: alpha(1)-Adrenergic vasoconstriction during dynamic leg exercise is diminished in younger individuals, although the extent of this exercise-induced "sympatholysis" in the elderly remains uncertain. Thus, in nine young (25 +/- 1 yr) and six older (72 +/- 2 yr) healthy volunteers, we evaluated changes in leg blood flow (ultrasound Doppler) during blood flow-adjusted intra-arterial infusion of phenylephrine (PE; a selective alpha(1)-adrenergic agonist) at rest and during knee-extensor leg exercise at 20, 40, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 52 publications
3
41
0
Order By: Relevance
“…[33][34][35][36] This is supported by a human study, in which infusion of the a1-adrenergic receptor agonist, phenylephrine, in young (mean age: 25.1 years) and old (mean age: 72.2 years) subjects at rest caused a less pronounced vasoconstriction response in the leg arteries of the older subjects. 37 Therefore, a higher a1-adrenergic receptor density would render peripheral arteries more sensitive to serum calcium. Not surprisingly, calcium infusion in humans also raised systolic and diastolic blood pressure and total peripheral resistance in both hypertensive and normotensive subjects with no change in cardiac output, and infusion of the calcium channel blocker, verapamil, attenuated this increase in both total peripheral resistance and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36] This is supported by a human study, in which infusion of the a1-adrenergic receptor agonist, phenylephrine, in young (mean age: 25.1 years) and old (mean age: 72.2 years) subjects at rest caused a less pronounced vasoconstriction response in the leg arteries of the older subjects. 37 Therefore, a higher a1-adrenergic receptor density would render peripheral arteries more sensitive to serum calcium. Not surprisingly, calcium infusion in humans also raised systolic and diastolic blood pressure and total peripheral resistance in both hypertensive and normotensive subjects with no change in cardiac output, and infusion of the calcium channel blocker, verapamil, attenuated this increase in both total peripheral resistance and blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with these previous findings, the present investigation has documented that resting LBF and LVC in the old were ϳ30% and ϳ35% less than in the young, respectively, and this was independent of body posture. While reductions in LBF and LVC have been further evidenced during a variety of active exercise modalities (11,26,37,54,56), the complexity of physiological mechanisms associated with muscle contraction make it difficult to isolate the contribution of limb movement on limb hyperemia.…”
Section: Age and Attenuated Skeletal Muscle Blood Flow During Rest Anmentioning
confidence: 99%
“…While LBF and LVC during exercise are also attenuated with age (11,26,37,56), due to the complexity of the physiological responses to exercise, the mechanisms responsible for age-related reductions in leg hyperemia are not fully understood.…”
mentioning
confidence: 99%
“…Indeed, ␣-adrenergic blockade with phentolamine restores the attenuated leg blood flow in aged individuals, although a vasodilatory effect of similar magnitude was observed in the young (9). Despite enhanced MSNA in the aged, further sympathetic stimulation tends to have a reduced vasoconstrictor effect in aged compared with young individuals (53,67). Parker et al (53) observed reduced sympathetic vasoconstrictor activity upon a vasodilatory stimulus of the popliteal artery in aged vs. young women, while Wray et al (67) showed that aged men vasoconstrict less than young men upon ␣ 1 -agonism of the femoral artery.…”
Section: Discussionmentioning
confidence: 97%
“…Despite enhanced MSNA in the aged, further sympathetic stimulation tends to have a reduced vasoconstrictor effect in aged compared with young individuals (53,67). Parker et al (53) observed reduced sympathetic vasoconstrictor activity upon a vasodilatory stimulus of the popliteal artery in aged vs. young women, while Wray et al (67) showed that aged men vasoconstrict less than young men upon ␣ 1 -agonism of the femoral artery. No preexercise training age-associated alterations of ␣-adrenergic-mediated nutritive muscle blood flow were observed in the present study.…”
Section: Discussionmentioning
confidence: 99%